Systemic Approach and Use of Models for Rehabilitation of Degraded Areas (Global Journal of Science Frontier Research, 2023)
Based on general systems theory, in Optical Chaos Theory and aided by the Systems Engineering has developed an ecological model system for the environmental recovery treating the area as a complex dynamic system, hypersensitive to initial conditions to prepare the ground. Assuming that the degraded areas are hypersensitive to the initial conditions of soil preparation, we applied the technique to trigger the roughness over time emergent properties that speed up the process of environmental recovery. Was evaluated in the process of the evolution of environmental restoration components, soil, vegetation, wildlife, water and microclimate under the effect of roughness, as auxiliary components in the internalization of matter and energy in the degraded area. We compared the evolution of biotic and abiotic environmental variables in the model preparation of rugged terrain with the conventional model, consisting of flat surfaces and more regular. It was confirmed that the roughness behave as gravitational attractor generated islands of diversity, the system incorporates a dynamic hypersensitive to these initial conditions and act as nucleation triggering effect amplified by the feedback, which increase and accelerate the recovery environment.
Keywords: environmental recovery; ecological model and systems general theory